Impact of Reagent Lot-to-Lot Variation on Internal Quality Control Results in Thyroid Hormone Analysis: A Retrospective Laboratory Study (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Reagent lot-to-lot variation is a recognized source of analytical variability in immunoassays. The magnitude and clinical relevance of this phenomenon are underexplored in routine laboratory practice. Methods: This retrospective study analyzed internal quality control data for FT3, FT4, and TSH over a period of 12 months. Bias resulting from reagent lot shift was calculated by comparing mean QC values between shifting reagent lots. Both directional and absolute bias were calculated. Results: The mean bias was 1.05% for FT3, 1.20% for FT4, and 0.83% for TSH. Despite low mean bias, substantial variability was observed, with mean absolute bias ranging from 5.08% to 6.01%. TSH demonstrated the highest maximum bias (15.06%). No consistent concentration-dependent pattern was observed across QC levels. Conclusion: Reagent lot transitions introduced non-directional random variability in thyroid hormone analysis. The variability was often large enough to be clinically significant. These findings highlight the need for robust lot verification protocols to ensure analytical consistency and accurate clinical interpretation.Bangladesh J. Nuclear Med. 28(2): 263-269, July 2025